Description of Haplothrips (Trybomiella) mateolanus n.sp. from the "calanchi" of Basilicata (Thysanoptera Phlaeothripidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
This new species does commonly occur on bushes of Atriplex halimus Linne(Chenopodiaceae). Its subgeneric feature is the lack of duplicated cilia in theforewings. Both females and males are macropterous, bicoloured, similar in bodyshape. Male size is lower.Ground colour and major setae are yellowish; head, pronotum, mesonotum, forefemora, apex of mid- and hindfemora, base of mid- and hindtibiae, tergite X andtube are brown; antennae are yellow, with segments I and VIII and base ofsegments II and VII brown; wing membranes are uncoloured; setae of fringes areyellow. Head is longer than broad. Compound eyes do not extend ventrally. Maxillarystylets arise at level of the posterior margin of eyes. Maxillary bridge isdistinct. Antennae are 8-segmented; segment III bears 2 sense cones; segment IVbears 4 sense cones; segment III is about as long as the IV and asymmetrical.Prothorax exhibits: epimeral sutures complete, major setae capitate, anteromarginalsetae short and pointed, medial-lateral setae rather short, basantra distinct.Metathorax lacks stemopleural sutures; metanotum reticulation is weak. Fore tarsiare toothed. Forewings lack duplicated cilia; sub-basal setae are capitate; distalcilia of fringes are thinner than the others and smooth. Pelta is vaguely triangular,irregular at sides, and bears 1 pair of campaniform sensilla. Tergites II-VII exhibit:2 pairs of sigmoid setae, 1 pair of campaniforrn sensilla and 1 pair of minor setaeon median area. Tube is short and conical.In females, setae B 1, B2 and B3 of tergite IX are acute and nearly reach the lengthof the tube. In males, setae B2 are short and stout. Aedeagus is rod-like, sinuate at sides, moderately enlarged and rounded at apex. Female holotype measures aregiven.
Keywords: taxonomy; subgeneric features; Southern Italy